Digital Technology Integration in Engineering Graphics and Design Education: A Qualitative Study of Teachers’ Pedagogical Practices and Challenges - Lutho Mteleli; Thokozani Isaac Mtshali; Ndlelehle Skosana (Journal of Education and Teaching (JET), 2026)
This study investigates the use of digital and educational technology tools in Engineering Graphics and Design (EGD) lessons in response to the Department of Education’s call for effective technology integration in schools. The study addresses a knowledge gap regarding how EGD teachers utilise available technologies to achieve intended learning outcomes, while also examining the challenges, successes, and pedagogical strategies involved. A qualitative research design was employed, using semi-structured interviews, non-participant classroom observations, and equipment analysis. Purposive sampling was used to select six EGD teachers and seventy-two learners. Guided by the Technological Pedagogical Content Knowledge (TPACK) framework and constructivist pedagogy, the findings reveal that teachers commonly used smart boards, projectors, and internet-based resources to support demonstrations and visualisation of complex drawings. However, technology integration remained largely supplementary rather than transformative, as digital tools were often used only after traditional lecture-based instruction. The study concludes that EGD teachers have not yet fully integrated technology into lesson planning and delivery. It recommends targeted professional development to promote transformative digital pedagogy and continuous reflective teaching practices.